Peran Program Maghrib Mengaji dalam Mengurangi Aktivitas Negatif Anak di Desa Ujung Negeri Kahan - Fauziah Nasution; Rahmi Aulia; Siti Khairuna Salwa Lubis; M. Iqbal Ritonga; Sofi Mayla Humairah (Pusat Riset dan Inovasi Nasional, 2026)
The phenomenon of moral degradation and the increase in negative activities among children during the crucial hours between dusk and evening have become serious challenges for the community in Ujung Negeri Kahan Village. This community service research aims to evaluate and optimize the role of the